Method for preparing uniform and refined intermediate alloy based on multiple physical outfields

The preparation of Al-Ti-CNTs intermediate alloys through multi-physical field composite technology has solved the problems of uneven refining and unstable performance of existing intermediate alloy refining agents when used in aluminum alloys, and achieved uniform fineness of aluminum alloy grains and improve material performance.

CN119410936APending Publication Date: 2025-02-11ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411594378.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

When used in aluminum alloys, existing intermediate alloy refining agents have problems such as uneven refinement, uneven grain size, and differences in performance, resulting in unstable material performance.

Method used

Multiphysical external field composite technology is used to prepare Al-Ti-CNTs intermediate alloy through ultrasonic electromagnetic composite, significantly refine the grain size of the aluminum alloy and improve its comprehensive mechanical properties.

Benefits of technology

The uniform refinement of aluminum alloy grains is achieved, the comprehensive mechanical properties of the material are improved, and the performance stability and uniformity of the material are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410936A_ABST
    Figure CN119410936A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a uniform and refined intermediate alloy based on a multi-physical external field, which comprises the following steps of: mixing and heating Al powder, Ti powder and CNTs (Carbon Nanotubes) powder serving as raw materials to obtain a melt, synchronously applying intermittent electromagnetic stirring to the melt, extending an ultrasonic probe into the melt to perform intermittent ultrasonic treatment, refining the treated melt, and casting and molding to obtain the intermediate alloy. According to the method, the Al-Ti-CNTs intermediate alloy refiner with dispersed nano-particles and efficient refinement is prepared through in-situ synthesis through ultrasonic and rotating magnetic field dual physical external field composite intervention for the melt, and the Al-Ti-CNTs intermediate alloy refiner can be used for refining aluminum alloy grains and improving the comprehensive mechanical property of an aluminum alloy material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonferrous metal smelting, relates to a master alloy for smelting aluminum alloy, and in particular to a method for preparing a master alloy with high efficiency and uniform refining ability by utilizing multi-physical external field compounding. Background Art

[0002] Metal alloy materials have excellent physical, chemical and mechanical properties and have become the main materials used in modern industry. Among them, aluminum alloy has low density, good conductivity and strong corrosion resistance, and its application volume is second only to steel.

[0003] With the changes of the times and the development of industry, metal alloy materials are moving towards performance upgrades and lightweighting. The performance requirements for aluminum alloy materials are also increasingly tending towards high quality and diversification. By improving the uniformity of the structure to obtain uniform and fine equiaxed crystals, the performance of the alloy can be improved.

[0004] Grain refinement is the most convenient and efficient method to improve the performance of alloy materials. A large number of studies have shown that the performance of cast aluminum alloys with fine equiaxed crystals far exceeds that of unrefined cast aluminum alloys. Grain refinement can be achieved by using mechanical or external field stirring, adding alloying elements or rare earth elements for alloying, or even accelerating the solidification rate for rapid cooling. However, these methods also have some disadvantages. Mechanical stirring can easily introduce impurities, long-term application of external fields will cause excessive energy consumption, alloying will affect the original material composition system, and accelerating the cooling rate cannot guarantee the stability of the process.

[0005] Adding master alloy refiners to cast aluminum alloys is also the most commonly used and easily controlled method for grain refinement. After adding master alloys, more heterogeneous nucleation particles are generated in the melt, so that heterogeneous nucleation proceeds in large quantities, and TiB2, TiC, and Al3Ti particles in the melt will also block the continued growth of grains, accelerating the transformation of columnar crystals to equiaxed crystals.

[0006] However, when conventional Al-Ti-B grain refiners are used in aluminum alloys containing elements such as Si and Zr, Zr reacts with B to form ZrB2, which will adhere to the surface of TiB2, resulting in a decrease in nucleation particles, a lower refinement rate, and poisoning. As time goes by, the amount of TiB2 gradually decreases until it is all converted into ZrB2, the refiner effect is completely lost, and even the material properties deteriorate.

[0007] Although the newly developed Al-Ti-C master alloy partially solves the above problems, it is difficult to achieve the ideal refinement effect due to the poor wettability of Al and graphite, the generated TiC particles are easy to agglomerate, and the large size problem. Whether it is the newly developed Al-Ti-C or the conventional Al-Ti-B, as the master alloy exists in the melt for a longer time, TiC and TiB2 particles will sink and agglomerate to varying degrees, resulting in uneven distribution of refined particles in the melt, resulting in unsatisfactory refinement effect, insufficient matrix performance or uneven performance.

[0008] Jiang et al. (Al-Ti-C master alloy with nano-sized TiC particles dispersed in the matrix prepared by using carbon nanotubes as C source., Journal of Alloys and Compounds, 748(2018), 774e782.) used finer CNTs to replace the ordinary graphite carbon source in the Al-Ti-C master alloy. Due to the unique structure of CNTs, the average size of TiC was significantly reduced after the reaction, and the carbon utilization rate was significantly improved. However, the problems of agglomeration and uneven size distribution were still not solved, and the problem of uneven refinement still existed.

[0009] Zhao et al. (Wetting of aluminium and carbon interface during preparationof Al-Ti-C grain refiner under ultrasonic field., Ultrasonics Sonochemistry, 76 (2021, 105633.) used ultrasonic composite intermediate alloy and found that the addition of ultrasound promoted the reaction and increased the number of TiC particles generated, but a small number of large-sized particles still existed.

[0010] Li et al. (Morphological and crystallographic characterization ofsolidified Al-3Ti-1B master alloy under a high magnetic field., MaterialsCharacterization, 95(2014), 1-11.) added magnetic field stirring during the preparation process. Under the action of the Lorentz magnetic force in the magnetic field, the particles flowed and broke with the melt, and the distribution became more uniform. The refinement ability was improved, but it still did not reach the ideal particle distribution state and refinement ability.

[0011] Since the use of intermediate alloy refiners may lead to problems such as uneven refinement, uneven grain size, and differences in performance, intermediate alloys cannot be used on a large scale. Summary of the invention

[0012] In order to overcome the shortcomings of the above-mentioned intermediate alloy refiners, the present invention proposes a method for preparing uniformly refined intermediate alloys based on multi-physical external fields, and prepares Al-Ti-CNTs intermediate alloys with high-efficiency refining ability through ultrasonic and electromagnetic composite, which significantly refines the grain size of aluminum alloys and improves the comprehensive mechanical properties of aluminum alloys.

[0013] To achieve the above-mentioned purpose, the method for preparing uniform and refined master alloy based on multi-physical external field of the present invention specifically comprises:

[0014] S1, Al powder, Ti powder and CNTs powder are used as raw materials, and the mixture is mixed and vacuum ball milled to obtain a mixed powder, wherein the Al powder accounts for 30-50wt% of the mixed powder, and the Ti / C ratio satisfies (4-10):1;

[0015] S2, placing the mixed powder in a vacuum furnace, heating it to 700-1400°C and keeping it warm to obtain a melt;

[0016] S3, applying intermittent electromagnetic stirring to the melt, and inserting an ultrasonic probe into the melt for intermittent ultrasonic treatment;

[0017] S4, refining the treated solution and casting it to obtain an intermediate alloy.

[0018] The raw materials Al powder, Ti powder and CNTs powder used in the present invention are all fine powders with a particle size of no more than 300 μm.

[0019] The raw materials Al powder, Ti powder and CNTs powder are dried in advance, and preferably, each raw material is dried at 100-150° C. for 2-4 hours.

[0020] Furthermore, in the present invention, the raw materials are preferably mixed and then vacuum ball-milled at 50 to 300 rpm for 30 to 120 minutes.

[0021] Furthermore, the present invention wraps the mixed powder obtained by vacuum ball milling with aluminum foil to prevent oxidation.

[0022] Furthermore, the intermittent electromagnetic stirring method is specifically to stir for 3 to 5 minutes, stop for 5 to 10 minutes, and repeat 4 to 10 times.

[0023] Furthermore, the intermittent ultrasonic treatment is specifically carried out by ultrasonicating for 3 to 5 minutes, stopping for 5 to 10 minutes, and repeating 4 to 10 times.

[0024] Furthermore, in the present invention, the electromagnetic stirring and ultrasonic treatment are preferably performed synchronously, the ultrasonic treatment is performed while the electromagnetic stirring is performed, and the electromagnetic stirring and the ultrasonic treatment are stopped at the same time.

[0025] Preferably, the total time of ultrasonic treatment and electromagnetic stirring of the melt in the present invention should be no less than 20 minutes.

[0026] Preferably, the equipment parameters of the electromagnetic stirring in the present invention are 300-500A and 3-5Hz; the equipment parameters of the ultrasonic treatment are 5-20Khz.

[0027] The present invention proposes a new method for preparing a master alloy refiner by using multiple physical external fields, and obtains an Al-Ti-CNTs master alloy refiner with dispersed nanoparticles and high efficiency refinement by in-situ synthesis through the combined intervention of dual physical external fields of ultrasound and rotating magnetic field on the melt. It is used to refine aluminum alloy grains and improve the comprehensive mechanical properties of aluminum alloy materials.

[0028] The present invention applies a multi-physical external field during the reaction process. Based on the Lorentz force and cavitation acoustic flow effect of the external field, the large and agglomerated TiC particles in the melt are dispersed, and the size is changed from micron to submicron or nanometer, and evenly distributed in the melt. The long strip Al3Ti particles are broken, and the diameter of the nucleation particles is reduced and the number is increased. Ultrasonic treatment solves the problem of poor wettability between CNTs and Al. The rotating magnetic field accelerates the flow of the melt, accelerates the reaction and makes the reaction thorough. The effective particles formed are constantly moving, and long-term sedimentation is also avoided.

[0029] Through the action of the physical external field, the particle distribution of the intermediate alloy refiner prepared by the present invention is more dispersed, thereby obtaining a better refinement effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is the SEM image of TiC distribution of the master alloy under different physical external fields.

[0031] Figure 2 yes Figure 1 High magnification SEM image of TiC distribution in the sample.

[0032] Figure 3 It is the grain diagram of pure aluminum after being refined by the intermediate alloy refiner under the action of different physical external fields.

[0033] Figure 4 This is a trend chart of hardness differences at sampling positions of ZL205A alloy after being refined with different master alloy refiners. Implementation

[0034] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0035] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0036] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example

[0037] Example 1

[0038] Weigh 50 g of Al powder, 40 g of Ti powder, and 10 g of CNTs powder, which were dried in an oven at 120°C for 2 h, respectively, and place them in a ball mill. Add grinding balls at a ball-to-material ratio of 6:1, evacuate for 10 min, and ball mill at 50 rpm for 30 min. Then take out the powder and wrap it with aluminum foil.

[0039] The powder wrapped in aluminum foil is placed in a vacuum furnace in an oxygen-free environment, and the temperature is raised to 1200° C. and maintained to obtain a solution.

[0040] A refining agent is added to the melt for refining to remove impurities on the melt surface, and the melt is cast into a metal mold to obtain an intermediate alloy A.

[0041] Example 2

[0042] Weigh 50 g of Al powder, 40 g of Ti powder, and 10 g of CNTs powder, which were dried in an oven at 120°C for 2 h, respectively, and place them in a ball mill. Add grinding balls at a ball-to-material ratio of 6:1, evacuate for 10 min, and ball mill at 50 rpm for 30 min. Then take out the powder and wrap it with aluminum foil.

[0043] The powder wrapped in aluminum foil is placed in a vacuum furnace in an oxygen-free environment, and the temperature is raised to 1200° C. and maintained to obtain a solution.

[0044] The ultrasonic probe was fully inserted into the melt, and the melt was treated with an ultrasonic frequency of 20 kHz. Ultrasonication was performed for 5 minutes and then stopped for 10 minutes, and this process was repeated 4 times.

[0045] After 1 hour, a refining agent is added to the solution for refining to remove impurities on the surface of the solution, and the solution is cast into a metal mold to obtain an intermediate alloy B.

[0046] Example 3

[0047] Weigh 50 g of Al powder, 40 g of Ti powder, and 10 g of CNTs powder, which were dried in an oven at 120°C for 2 h, respectively, and place them in a ball mill. Add grinding balls at a ball-to-material ratio of 6:1, evacuate for 10 min, and ball mill at 50 rpm for 30 min. Then take out the powder and wrap it with aluminum foil.

[0048] The powder wrapped in aluminum foil is placed in a vacuum furnace in an oxygen-free environment, and the temperature is raised to 1200° C. and maintained to obtain a solution.

[0049] The melt was subjected to electromagnetic stirring treatment using a 300A, 5Hz electromagnetic stirring device, stirring for 5 minutes and stopping for 10 minutes, and repeated 4 times.

[0050] After 1 hour, a refining agent is added to the solution for refining to remove impurities on the surface of the solution, and the solution is cast into a metal mold to obtain an intermediate alloy C.

[0051] Example 4

[0052] Weigh 50 g of Al powder, 40 g of Ti powder, and 10 g of CNTs powder, which were dried in an oven at 120°C for 2 h, respectively, and place them in a ball mill. Add grinding balls at a ball-to-material ratio of 6:1, evacuate for 10 min, and ball mill at 50 rpm for 30 min. Then take out the powder and wrap it with aluminum foil.

[0053] The powder wrapped in aluminum foil is placed in a vacuum furnace in an oxygen-free environment, and the temperature is raised to 1200° C. and maintained to obtain a solution.

[0054] The ultrasonic probe was fully inserted into the melt, and while applying an ultrasonic frequency of 20 KHz, the melt was subjected to electromagnetic stirring using a 300A, 5 Hz electromagnetic stirring device. The mixture was stirred and ultrasonicated for 5 minutes, then stopped for 10 minutes, and repeated 4 times.

[0055] After 1 hour, a refining agent is added to the solution for refining to remove impurities on the surface of the solution, and the solution is cast into a metal mold to obtain an intermediate alloy D.

[0056] Figure 1 The SEM images of the intermediate alloys A to D prepared above show the distribution of TiC under different physical external fields.

[0057] Without applying any physical external field, the TiC agglomerates generated in situ in the intermediate alloy A were distributed to form agglomerates of different sizes. In the intermediate alloy B, based on the cavitation acoustic streaming effect of ultrasound, the agglomerates in most areas treated with ultrasound were dispersed, but due to the limitation of ultrasound in the melt, the agglomerates in the ultrasonic probe area were effectively dispersed, while the dispersion effect was poor in areas far from the probe. After electromagnetic stirring alone, the melt of the intermediate alloy C flowed in the crucible under the action of the Lorentz force, and the agglomerates changed from spherical to long strips. Under the simultaneous application of ultrasound and electromagnetic stirring, the agglomerates in the ultrasonic probe area of ​​the intermediate alloy D were dispersed, and moved away from the probe position with the movement of the melt, and new agglomerates were dispersed near the probe with the flow of the melt.

[0058] Furthermore, Figure 1 After magnification 100 times, observe the TiC particles in the master alloy at high magnification, see Figure 2 Compared with the blank (A), (B) showed no obvious change after applying only the ultrasonic external field, (C) showed a more uniform distribution of particles under the electromagnetic external field, but there were also some large-sized particles; (D) showed a dense distribution of particles after applying both electromagnetic and ultrasonic fields, and the large-sized particles were shattered by ultrasonic waves. The number of TiC particles generated under the dual physical external fields was the largest, and the sizes were close, without obvious agglomeration.

[0059] Through the simultaneous application of the above dual physical external fields, the agglomerates in the master alloy are completely dispersed.

[0060] Application Example 1

[0061] Weigh 2 kg of industrial pure aluminum, wash and dry it, place it in a resistance furnace, heat it to 780°C and keep it warm for 30 minutes to obtain aluminum melt.

[0062] 10 g of each of the four intermediate alloys of Examples 1 to 4 were weighed, dried, added to the aluminum melt, stirred evenly, and then heated to 730° C. for refining. The scum was removed and the temperature was lowered to 710° C. for casting to obtain an aluminum alloy.

[0063] At the same time, a blank aluminum alloy was obtained by refining the aluminum melt without adding any intermediate alloy and then casting it as a control.

[0064] Figure 3The macroscopic grain diagrams of the above five aluminum alloys are given. Among them, the pure aluminum grains of (A) are composed of wide and long columnar crystals, and some columnar crystals grow from the outside to the center. (B) After adding the intermediate alloy without physical external field treatment, the grains are effectively refined, but the grain distribution is extremely uneven. There are some large-sized equiaxed crystals in the center, and the outside is still columnar crystals. The sizes of these columnar crystals are different and are smaller than those of pure aluminum. After adding the intermediate alloys treated with ultrasound or electromagnetic alone, large-scale equiaxed crystals appeared in the center of (C) and (D), and the equiaxed crystal size of the intermediate alloy treated with electromagnetic force was significantly smaller than that of the pure aluminum grains of the intermediate alloy treated with ultrasonic force (C); among them, the outer part of the pure aluminum grains of the intermediate alloy treated with ultrasonic force (C) still showed obvious columnar crystal characteristics, but the size was greatly reduced compared with pure aluminum or pure aluminum grains added with intermediate alloys that were not treated with external field. However, the pure aluminum grains of the intermediate alloy treated with electromagnetic stirring (D) were basically transformed into equiaxed crystals, and only small-sized columnar crystals appeared in the outermost part.

[0065] After adding the intermediate alloy treated by ultrasonic and electromagnetic composite treatment, the pure aluminum grains in (E) were further refined, the columnar crystals basically disappeared, and all were transformed into equiaxed crystals. The grain size distribution was uniform, and there was no obvious grain size segregation phenomenon, achieving the most ideal refinement effect.

[0066] Application Example 2

[0067] For commercial aluminum alloys, the grains have been initially refined based on the various alloys and rare earth elements in their composition. Adding a master alloy refiner may not produce a significant change in grain size similar to pure aluminum, but grain refinement will increase the strength of the matrix material. Therefore, this application example tests the grain refinement and uniformity of different master alloys by measuring the hardness index at different sampling positions.

[0068] 2 kg of ZL205A aluminum alloy was weighed, washed and dried, placed in a resistance furnace, heated to 780°C and kept warm for 30 min to obtain an aluminum alloy melt.

[0069] 10 g of each of the four intermediate alloys of Examples 1 to 4 were weighed, dried, added to the aluminum alloy melt, stirred evenly, and then heated to 730° C. for refining. The scum was removed and the temperature was lowered to 710° C. for casting to obtain the aluminum alloy.

[0070] At the same time, a blank aluminum alloy was obtained by refining the aluminum melt without adding any intermediate alloy and then pouring it as a control.

[0071] Six samples were evenly taken from the cast Y-shaped block, and the Vickers hardness of the samples was measured according to the GB / T 4340.1-2024 method. The specific test results are listed in Table 1.

[0072]

[0073] In Table 1, the average cast hardness of ZL205A alloy without adding intermediate alloy is 60.7Hv, and the difference between its maximum and minimum values ​​is only 4.3. After applying intermediate alloy A without physical external field treatment, the average hardness is slightly increased to 61.5Hv, but the maximum difference is increased to 7.8, the maximum value has reached 65.2Hv, and the minimum value is only 57.4Hv. Large hardness differences will lead to instability of the material during service. After adding intermediate alloys C and D treated with ultrasound or electromagnetic alone, the hardness of the material is increased to 62.2Hv and 64.7Hv respectively, but the maximum difference is 5.4 and 4.5 respectively. After adding the intermediate alloy treated with ultrasound and electromagnetic composite, the hardness of the material is increased to 65.2Hv, the maximum difference is only 3.7, and the maximum and minimum values ​​are 66.7Hv and 63.4Hv respectively.

[0074] Further through Figure 4 It can intuitively reflect the uniformity of hardness at different positions of the material. The addition of the intermediate alloy treated with dual physical external fields can achieve the improvement of hardness while ensuring good uniformity, meeting the service status of the material and ensuring service stability.

[0075] Example 5

[0076] Weigh 50 g of Al powder, 45 g of Ti powder and 5 g of CNTs powder, which were dried in an oven at 100°C for 4 h, respectively, and put them into a ball mill. Add grinding balls at a ball-to-material ratio of 6:1, evacuate for 10 min, ball mill at 50 rpm for 30 min, then take out the powder and wrap it with aluminum foil.

[0077] The powder wrapped in aluminum foil is placed in a vacuum furnace in an oxygen-free environment, and the temperature is raised to 1100° C. and maintained to obtain a solution.

[0078] The ultrasonic probe was fully inserted into the melt, and while applying an ultrasonic frequency of 20 KHz, the melt was subjected to electromagnetic stirring using a 400A, 3 Hz electromagnetic stirring device. The stirring and ultrasonication were performed for 3 minutes, and then stopped for 5 minutes. This was repeated 10 times.

[0079] A refining agent is added to the melt for refining to remove impurities on the melt surface, and the melt is cast into a metal mold to obtain an intermediate alloy.

[0080] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a uniform and refined master alloy based on a multi-physical external field, comprising: S1, Al powder, Ti powder and CNTs powder are used as raw materials, and the mixture is mixed and vacuum ball milled to obtain a mixed powder, wherein the Al powder accounts for 30-50wt% of the mixed powder, and the Ti / C ratio satisfies (4-10):1; S2, placing the mixed powder in a vacuum furnace, heating it to 700-1400°C and keeping it warm to obtain a melt; S3, applying intermittent electromagnetic stirring to the melt, and inserting an ultrasonic probe into the melt for intermittent ultrasonic treatment; S4, refining the treated solution and casting it to obtain an intermediate alloy.

2. The method according to claim 1, characterized in that The raw materials Al powder, Ti powder and CNTs powder are all fine powders with a particle size not greater than 300 μm.

3. The method according to claim 1, characterized in that The method also includes pre-drying the raw materials Al powder, Ti powder and CNTs powder respectively, and drying each raw material at 100-150° C. for 2-4 hours.

4. The method according to claim 1, characterized in that After mixing the raw materials, vacuum ball mill at 50-300 rpm for 30-120 min.

5. The method according to claim 1, characterized in that The mixed powder obtained by vacuum ball milling was wrapped with aluminum foil.

6. The method according to claim 1, characterized in that The intermittent electromagnetic stirring method is to stir for 3 to 5 minutes, stop for 5 to 10 minutes, and repeat 4 to 10 times.

7. The method according to claim 1, characterized in that The intermittent ultrasonic treatment method is to ultrasonicate for 3 to 5 minutes, stop for 5 to 10 minutes, and repeat 4 to 10 times.

8. The method according to claim 1, 6 or 7, characterized in that The electromagnetic stirring is performed synchronously with the ultrasonic treatment, the electromagnetic stirring is performed simultaneously with the ultrasonic treatment, and the electromagnetic stirring and the ultrasonic treatment are stopped simultaneously.

9. The method according to claim 1, 6 or 7, characterized in that The total time of ultrasonic treatment and electromagnetic stirring of the melt is not less than 20 minutes.

10. The method according to claim 1, characterized in that The parameters of the electromagnetic stirring equipment are 300-500A, 3-5Hz, and the parameters of the ultrasonic treatment equipment are 5-20Khz.